2018
DOI: 10.1111/imr.12643
|View full text |Cite
|
Sign up to set email alerts
|

ILC2 memory: Recollection of previous activation

Abstract: Immunological memory, traditionally thought to belong to T and B cells, has now been extended to innate lymphocytes, including NK cells and ILC2s, myeloid cells such as macrophages, also termed "trained immunity" and more recently to epithelial stem cells. In this review, we discuss the mechanisms underlying memory generation on ILC2s and speculate about their potential role in human allergic diseases, such as asthma. Moreover, we examine the relevance of the spontaneous ILC2 activation in the lung during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 74 publications
2
22
0
Order By: Relevance
“…Yet another organizing principle for the presentation of the articles in this volume is the preferred temporospatial context explored for immunological memories. An emphasis on anatomic niches such as primary and secondary lymphoid organs, non‐lymphoid tissues including tumors is accompanied by temporal considerations that range from details of T‐ and B‐cell memory generation and maintenance to evolution at large . Altogether, we agree with the conclusion proposed in the introductory review; that immunologic memory is best conceived of as a multi‐dimensional concept with physical correlates in far more components of the adaptive and innate immune system than previously appreciated.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Yet another organizing principle for the presentation of the articles in this volume is the preferred temporospatial context explored for immunological memories. An emphasis on anatomic niches such as primary and secondary lymphoid organs, non‐lymphoid tissues including tumors is accompanied by temporal considerations that range from details of T‐ and B‐cell memory generation and maintenance to evolution at large . Altogether, we agree with the conclusion proposed in the introductory review; that immunologic memory is best conceived of as a multi‐dimensional concept with physical correlates in far more components of the adaptive and innate immune system than previously appreciated.…”
supporting
confidence: 82%
“…This is perhaps best illustrated by the prominence of “memory inflation,” the numerical expansion of virus‐specific memory T cells in certain experimental and naturally occurring scenarios as emphasized by several contributors . At the same time, the very concept of “immunological memory” has undergone a substantial “inflation” (as it were) of its own, being now invoked for cell types other than T and B cells (innate lymphocytes, monocyte/macrophages) and species other than vertebrates (invertebrates, plants, archaea, and bacteria) . Another topic extensively discussed throughout this issue is the role of persisting antigen in shaping immunological memory in the context of chronic viral infections, cancer and the preservation of protective immunity .…”
mentioning
confidence: 99%
“…Martinez‐Gonzalez et al. propose that these iILC2 cells are not resident in the lung and rather migrate from the gut . Lastly, skin ILC2s have been shown to have high expression of ST2, whereas other studies show that skin ILC2 activation is TSLP mediated and independent of IL‐33 .…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence points towards the role of RAG‐1 in acquiring the memory features of NK cells another study demonstrated a transient expression of the RAG1 gene in mouse ILC2s during development . Preliminary data show that long‐term memory ILC2 responses are impaired in Rag 1 −/− mice, however, the absence of T and B lymphocytes may be relevant during the secondary challenge of memory‐like ILC2s . Other markers implicated in activation and memory functions in T cells are CD45RA and CD45RO.…”
Section: Memory Ilc2smentioning
confidence: 94%